2010
DOI: 10.1038/jp.2010.78
|View full text |Cite
|
Sign up to set email alerts
|

Comparable effect of conventional ventilation versus early high-frequency oscillation on serum CC16 and IL-6 levels in preterm neonates

Abstract: Objective: Clara cell 16 kD protein (CC16) and interleukin (IL)-6 have been used as peripheral blood biomarkers of alveolar leakage and inflammation, respectively. Thus, their measurement in the bloodstream could be used to assess ventilator-induced lung injury. The objective of this study was to evaluate the effect of optimized synchronized intermittent mandatory ventilation (SIMV) and high-frequency oscillatory ventilation (HFOV) on circulating CC16 and IL-6 levels when used as the initial ventilation modes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
7
2
Order By: Relevance
“…Although previous studies have revealed a relatively stable median CC16 level in normal controls (5-7 ng/ml), the median CC16 value of critical care patients in our control group appeared to be higher (22.23 ± 13.28 ng/ml), probably because clinical conditions such as mechanical ventilation or primary graft dysfunction might promote the production of CC16 [28,29]. This could have led to an unavoidable selection bias.…”
Section: Discussioncontrasting
confidence: 59%
“…Although previous studies have revealed a relatively stable median CC16 level in normal controls (5-7 ng/ml), the median CC16 value of critical care patients in our control group appeared to be higher (22.23 ± 13.28 ng/ml), probably because clinical conditions such as mechanical ventilation or primary graft dysfunction might promote the production of CC16 [28,29]. This could have led to an unavoidable selection bias.…”
Section: Discussioncontrasting
confidence: 59%
“…[26][27][28][29] Comparisons of lung injury following HFOVand CV vary. Various reports indicate either (1) little difference in the alveolar leakage and systemic inflammation in neonates, 30 (2) attenuation of early activation of inflammation and clotting in preterm lambs during HFOV when compared to CV 31 and (3) reduced pro-inflammatory cytokines in HFOV treated neonates compared to CV. 32 There are fewer studies comparing lung injury during HFJV to other ventilator modalities, but a comparison of HFJV and HFOV in rabbits showed a clear reduction in lung injury following HFJV.…”
Section: Discussionmentioning
confidence: 99%
“…The studies of very preterm newborns, which have also documented systemic inflammation associated with ventilation, have been limited in the number of subjects and the number of indicators of inflammation [9-13]. …”
Section: Introductionmentioning
confidence: 99%